Application Of “Stunting Prevention” Android-Based Applications To Mother Knowledege And Nutritional Status Of Toddlers Ages 0-36 Months - Ervin Rufaindah; Patemah Patemah (JURNAL KEBIDANAN, 2021)
Stunting is a growth disorder in children: the child’s height is lower or shorter (stunted) than the standard age. A serious condition that occurs when a person does not get the right amount of nutritional intake for a long time (chronic). Contributes to 15-17 percent of all child deaths. The impact of stunting is underachieving in school and being less productive as adults. When the baby has passed the age of 9 months, it is possible for the mother not to bring her child back to the health service so that there is no monitoring of the child’s development. This study utilizes an application “Stunting Prevention” which can be used by mothers to increase knowledge about how to prevent stunting. This study aims to determine the effect of the application of stunting prevention applications on maternal knowledge and nutritional status of children 0-36 months. The research design was a pre-experimental research design. This study uses the One Group Pretest-Posttest Design approach. The population in this study were mothers who have children aged 0-36 months in the Mojolangu Village, Malang City. The sampling technique used was purposive sampling. The results showed that there was an effect of using the application on maternal knowledge about stunting prevention with the results of wilcoxon analysis, namely 0,00 (0,05) and there was no effect of using the android application “Stunting Prevention” on the nutritional status of infants 0-36 months with a ρ value of 0,317 (0,05).